Computerized Testing Machines to Study the Effect of Strain Rate on Mechanical Properties of CFRP - Ali, Jaafar Kh.; Najim, Saleh I. (Basrah Journal for Engineering Sciences, 2016)
In this paper, a universal testing machine and an impact testing apparatus have been upgraded by using a high- accuracy data acquisition and control system interfaced to a personal computer with proper sensors and actuators. The purpose of upgrade is to increase the accuracy of the measurements and to perform advanced material testing procedures that are not possible with the old configuration. The modernization process not only permits the accurate data acquisition and convenient operation but also the ability to study the effect of strain rate on the tensile properties of materials. Also, an experimental study of the response of CFRP (Carbon Fiber Reinforced Plastic) material to low and intermediate strain rates has been carried out.